Pembelajaran Konsep Sudut Keliling pada Siswa Kelas VIII - Fitrianti, Yuli (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This research aims at producing learning procedure that can establish students’ comprehension on the concept of central and inscribed angle in a circle. This study is a Classroom Action Research. It is conducted to Eight Year Junior High School Students of MTs Al Ma’arif 01 Singosari Malang. The implementation of learning activities is exactly done as learning design that consists of five discourses. Each discourse has its own theme and purposes so they have different themes and purposes. All the themes are delivered in a cycle activity. The result is that the strategy used in this study succeeds as a learning procedure to establish students’ comprehension of that concept on eighth year junior high school students of MTs al Ma’arif 01 Singosari Malang.